Višestruki slojevi identiteta u romanu Gautama Malkanija Londonstanac (Philologia, 2021)
This paper analyses the complexities of multicultural society in contemporary London; it refers to a particular social and cultural milieu of the London borough of Hounslow as described in Gautam Malkani,s novel Londonstani. It also examines various aspects of national, subcultural, personal and group identity of the major characters in the novel.
Keywords: identitet; društvo; supkultura; tradicija; jezik; Britanci azijskog porekla